2008
DOI: 10.1590/s1415-47572008000200014
|View full text |Cite
|
Sign up to set email alerts
|

Supernumerary chromosomes in the pufferfish Sphoeroides spengleri: first occurrence in marine Teleostean Tetraodontiformes fish

Abstract: Cytogenetic analyses carried out in eight specimens of Sphoeroides spengleri revealed the presence of 2n = 46 chromosomes (20 M/SM and 26 ST/A). Besides the standard karyotypical set, the presence of B microchromosomes was observed in two individuals, ranging from 0 to 2 microchromosomes per cell. A karyotype composed by 2n = 46 chromosomes with occurrence of M and SM chromosomes is considered basal for the species from the clade comprising the families Tetraodontidae, Balistidae, and Diodontidae, although it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…They have been described for a large of number of plant and animal species (Jones & Rees, 1982;Camacho et al, 2000), and have been observed in more than 40 freshwater fish species (Oliveira et al, 2000). B chromosomes seem to be less frequent in marine fish and have been described in Upeneus parvus (Perciformes) (Pauls et al, 1996), Sphoeroides spengleri and Chilomycterus spinosus (Tetraodontiformes) (Alves et al, 2008;Noleto, 2009), among others.…”
Section: Introductionmentioning
confidence: 99%
“…They have been described for a large of number of plant and animal species (Jones & Rees, 1982;Camacho et al, 2000), and have been observed in more than 40 freshwater fish species (Oliveira et al, 2000). B chromosomes seem to be less frequent in marine fish and have been described in Upeneus parvus (Perciformes) (Pauls et al, 1996), Sphoeroides spengleri and Chilomycterus spinosus (Tetraodontiformes) (Alves et al, 2008;Noleto, 2009), among others.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative way of evolutionary dynamics would be the intense chromosomal rearrangements involved in genome size reduction in Tetraodontidae species, making a favorable condition for the origin and maintenance of B chromosomes (Martinez et al 2010). The micro Bs already were described for S. spengleri from Ubatuba Bay, São Paulo, Brazil (Alves et al 2008), fact that might indicate a common origin for these B chromosomes, hypothesis supported by the recent formation of Brazilian bays (Suguio et al 1985).…”
Section: Discussionmentioning
confidence: 96%
“…In neotropical fishes the occurrence the supernumerary chromosomes is a sporadic event, mainly in marine species (Pauls et al 1996). In Tetraodontiformes the unique reports about the presence of B chromosomes was in Sphoeroides spengleri from São Paulo Coast (Alves et al 2008) and in Canthigaster figueiredoi (Martinez et al 2010), both of the family Tetraodontidae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fishes, they have been already described in Characiformes (Mizoguchi & Martins-Santos, 1997;Voltolin et al, 2010), Labriformes (cited as Perciformes, Roncatti et al, 2007;Poletto et al, 2010), Siluriformes ShimabukuroDias et al, 2005;Blanco et al, 2012), Gymnotiformes (Mendes et al, 2012) and Tetraodontiformes (Alves et al, 2008).…”
Section: Introductionmentioning
confidence: 99%